Sejauh Mana Pembahasan Pasar Modal Syariah? : Sebuah Analisis Scientometric - Mughnii Kahila Shanty; Miftakhus Surur (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
This research aims to map the development of Islamic capital market research and trends, as well as how this topic is developing in various countries and the themes that dominate the literature based on journals indexed by Scopus. The method used is descriptive qualitative by analyzing data from 69 documents published from 2000 to the first quarter of 2024. For further analysis, researchers used Biblioshiny software, a free tool supported by R. The results show that discussions regarding the Islamic capital market are not only limited to in Muslim-majority countries, but also gets attention from non-Muslim countries. There are three topics related to sharia capital market trends, namely; The Role of the Government and Performance of the Sharia Index, Islamic Law on Sharia Capital Markets, and Investment and Economic Growth. The practical implications of this research can be utilized by investors, governments, regulators and companies or SMEs who can use the Islamic capital market as an instrument to seek capital for their businesses. Suggestions for further research could be to use a better database such as WoS for more comprehensive results.